Development of an enhanced component carrier selection algorithm in Long Term Evolution-Advanced with carrier aggregation - Al Katsha, Mhd Zaher (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Given that Long Term Evolution (LTE) does not meet the technical requirements of a Fourth Generation (4G) wireless service, the Third Generation Partnership Project (3GPP) organization introduces a new standard known as Long Term Evolution-Advanced (LTE-Advanced) so as to address the LTE limitations. LTE-Advanced is expected to deliver high speed multimedia services with an improved Quality of Service (QoS). Carrier Aggregation (CA) that aggregates multiple Component Carriers (CCs) of the same or different frequency bands, is one of the methods that allows the LTE-Advanced to deliver high speed multimedia services. At the early stage of transition towards 4G, the LTE-Advanced wireless system may contain a large number of legacy LTE users together with a number of LTE-Advanced users. Note that the LTE-Advanced users can transmit packets on all of the available CCs whereas the LTE users are limited to transmit packets on a single CC. As the legacy LTE users can support packets transmission on a single CC, a CC selection algorithm that is responsible to assign a CC to each newly-arrived legacy LTE users is becoming of paramount importance in the LTE-Advanced system. The existing CC selection algorithms cannot provide good capacity whilst maximizing the throughput and balancing the load. To address the stated limitations, this thesis proposes an enhanced CC selection algorithm that takes the channel quality and traffic load in each CC into consideration. It was shown via simulation that the proposed algorithm gives more than 40% improvement in maximizing the capacity when compared with the conventional CC selection c.